2010
DOI: 10.1007/s11307-010-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prion Deposits and Microglial Activation in Scrapie-Infected Mice Using Molecular Imaging Probes

Abstract: These findings indicate the ability of [(125)I]-IMPY and [(125)I]-CLINDE to evaluate prion deposits and microglial activation in vitro and ex vivo in scrapie-infected mice at different stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Thus, these three aspects of prion disease pathology appeared nearly simultaneously between 20 and 40 dpi. PrPres detection at 40 dpi in this system was 20 to 30 days earlier than in several previous studies (1,2,4,12,17,30). This might be due to the rapid tempo of the disease induced by our stock of strain 22L, which is known to induce clinical disease at 135 to 140 dpi and is about 15 days faster than our stocks of other scrapie strains, such as RML, ME7, and 79A.…”
Section: Discussioncontrasting
confidence: 44%
“…Thus, these three aspects of prion disease pathology appeared nearly simultaneously between 20 and 40 dpi. PrPres detection at 40 dpi in this system was 20 to 30 days earlier than in several previous studies (1,2,4,12,17,30). This might be due to the rapid tempo of the disease induced by our stock of strain 22L, which is known to induce clinical disease at 135 to 140 dpi and is about 15 days faster than our stocks of other scrapie strains, such as RML, ME7, and 79A.…”
Section: Discussioncontrasting
confidence: 44%
“…In addition, the distribution of activated microglial cells was consistent with the distributions of PrP Sc and dead neurons (17,18). These observations indicate that the activation of microglial cells serves an important role in the neuropathological changes of PrP-mediated scrapie infection (19). In the present study, microglial cells were activated by treatment with PrP, as demonstrated by the cell morphological changes.…”
Section: Discussionsupporting
confidence: 86%
“…From these, 22 novel radiotracers bearing carbon‐11 [11C], fluorine‐18 [18F] and iodine‐123 [123I] representing the imidazopyridines , [123I]CLINDE , [11C]CLINME and [123I]CLINME ; the structurally related imidazopyridazines , 2‐phenylpyrazolo[1,5‐a]pyrimidine acetamides and [123I] N,N‐dialkyl‐2‐phenylindol‐3‐yl‐glyoxylamides ; as well as the N‐benzyl‐N‐(2‐phenoxyaryl)‐acetamide derivatives, were prepared and extensively evaluated in rodents, with many of these compounds displaying improved biological characteristics, such as a higher target to background signal, faster clearance from nonspecific tissue and improved metabolic stability relative to [11C]PK11195 in in vivo animal studies . The imidazopyridines were the most successful; five of these radiotracers ([123I]‐CLINDE, [123I]‐CLINME, [11C]‐CLINME, [18F]‐PBR111 and [18F]‐PBR102) have further been evaluated in several rodent animal models of disease confirming that these radiotracers can image and measure activated microglia/macrophage infiltration in the CNS. In addition, we have combined and compared the results of in vitro ligand binding, autoradiography, RT‐qPCR (reverse transcription quantitative real‐time polymerase chain reaction) and immunohistochemical staining with in vivo small animal SPECT and PET imaging using our novel radiotracers [123I]CLINDE and [18F]PBR111 in models of multiple sclerosis in rodents (experimental autoimmune encephalomyelitis, EAE) .…”
Section: Tspo Ligand Developmentmentioning
confidence: 99%